The "anaerobic threshold" concept is not valid in physiology and medicine - Brooks, G. A. (Medicine & Science in Sports & Exercise, 2021)
Lactate is at the fulcrum of metabolism; hence, factors that affect lactate production exert extreme leverage on metabolic rate and energy substrate partitioning (1). Lactate is the main fuel energy source, the main gluconeogenic precursor, and a molecule that signals physiological adaptions to metabolic stress (2), and it directly as well as indirectly controls the use of other fuel energy sources such as free fatty acids (1). Lactate is produced and disposed of continuously under fully aerobic conditions from the moments of conception through the terminations of life (3). The rate of glycolysis leading to lactate production in influenced by variety of normal conditions that require ATP to support cell work in its various forms (4). Examples of aerobic glycolysis in vivo include sperm motility (5), the beating heart (6), cerebral executive function (7), and course working muscle (8). Signification advances in the field of lactate metabolism have been possible through the use of technologies such as isotope tracer methodology as applied to studies on mammalian animal models (9) and humans (10) and magnetic resonance spectroscopy (MRS) as applied to mammalian muscle (11). Isotope tracer and MRS technologies not only reveal that lactate production occurs under fully aerobic conditions but also that dynamic range of lactate metabolism far exceeds that of glucose and lipids. Greater lactate production than glucose disposal is attributable to the role of glycogen in providing substrate for glycolytic flux (1). Restated, low and stable tissue lactate levels belie high rates of lactate turnover (production and removal). Restated still another way, we cannot know lactate turnover, or for that matter turnover of any metabolite, from concentration measures alone.